Fear of Covid-19 Related Factors among Females in Indonesia: An Online Survey - Roxsana Devi Tumanggor; Intan Imaroh; Andrew Cashin (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: The COVID-19 pandemic is a highly infectious flu outbreak which spread rapidly around the world. COVID-19 outbreak caused panic and is predicted to increase the prevalence of mental illnesses such as depression and anxiety disorder . Along with increased anxiety and decreased mood, increased fear has been detected.